Liver hanging maneuver in laparoscopic right hepatectomy—still to be standardized - Llado, Laura; Mils, Kristel; Ramos, Emilio (Laparoscopic Surgery, 2018)
Weread with great interest the article by Kim describing pure laparoscopic righthepatectomy (LRH) using a modified liver hanging maneuver (LHM) and thetechnical evolution from caudal approach towards ventral approach (1). Theauthors described their technique in 2016 (2), and have used it for differenttypes of laparoscopic liver resections (LLR) (3-5). The modified LHM describedby Kim et al. (2) adds another solution to overcome the difficulties toperform a LRH. The different published options to perform LRH reflect the lackof standardization of the technique.